Experimental characterization of banana fiber reinforced polyester composites. (2022) - kalangi, Chaithanya; Antony Prabu, D.; Sujin Jose, A.; Jani, S.P.
Abstract: The mechanical characters of banana fiber extracted from different parts of the banana such as stem, pseudo and leaf vary significantly. Three different composites were prepared using the fibers of these three parts of the banana plant. The constant weight percentage of fiber content (40%) is maintained for all the composite specimens with unsaturated polyester resin. The mechanical characters of composite specimens made from the fibers taken from three parts of the banana tree are explored separately. Through the mechanical test, we found that the samples which are prepared with leaf fibers have better mechanical characters than the samples prepared by using other fibers.